Manajemen Program Kelas Tahfidz Dalam Meningkatkan Kualitas Hafalan Siswa Di SMA Muhammadiyah 1 Klaten - Ramadani, Amilia Rizka; Jinan, Mutohharun (Jayapangus Press, 2025)
This study aims to describe the process of planning, organizing, implementing, and assessing in an effort to improve the quality of student memorization in the Tahfidz class program at SMA Muhammadiyah 1 Klaten. The type of research used is qualitative research with a field research approach. The subjects involved in this study included the principal, Tahfidz coordinator, Tahfidz teacher, and students who participated in the Tahfidz program. Data were collected through observation, interview, and documentation techniques. Data analysis was conducted using an interactive method based on the Miles and Huberman model, while triangulation techniques were used to validate the data obtained. The results showed that the management of the Tahfidz program runs well, especially through cooperation with Griya Qur'an in the learning process. The program is carefully managed to support all stages of its implementation, in accordance with the predetermined objectives. The Tahfidz program management process includes planning which includes educators, selection of students, financing, learning materials, and activity procedures. Organizing is done by preparing an organizational structure in accordance with the duties and responsibilities of each party. Program implementation is carried out through Tahfidz learning activities, and assessment is carried out through several stages of assessment in the learning process that has been prepared previously.